Aportes del programa Centros Regionales de Educación Superior a la democratización de la educación superior en Colombia (2021)
This reflection article aims to establish the contributions to the democratization of higher education achieved during the development of the Regional Centers for Higher Education (CERES) strategy in Colombia, between 2003 and 2014. It is a critical reflection based on a documentary review, guided by an analysis of bibliographic trends. It is concluded that there is a bias defended by the Colombian State so far in the 21st century, in which coverage, from the perspective of supply and demand, was the main justification for promoting the CERES strategy, in the name of university democratization.